Model Inovasi Hibah dan Bansos Online Kota Bandung - Nugroho, Candra Setya; Setiawan, Wawan Dharma (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2017)
The management of grants and bansos funds has become a problem in several local governments. The problem of grant and bansos management is related to transparency and accountability. Bandung City Government seeks to improve its public services by innovating the management of grants and bansos through the media website called Sabilulungan or Grants and Bansos Online to solve the problem. Through this research there will be discussed related to the management model of grants and bansos through grants and online bansos. This research uses descriptive qualitative research method (more specifically with the method of "action research") to see clearly the management of grants and bansos melelui innovation grants and bansos online. Based on the results of this study found that this innovation is very beneficial in the management of grant funds and bansos mainly improve transparency and accountability. This innovation has a positive impact that can be replicated by other regions